Experimental device for testing permeability characteristics of undisturbed sandstone
By designing an experimental device including sample tank, moisture temperature sensor, water supply system and water collection bucket, the problem of priority flow and low accuracy of traditional methods when measuring arsenic sandstone is solved, and high-precision and visual measurement of the permeability characteristics of arsenic sandstone is achieved.
Patent Information
- Application Number
- CN202411849093.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-14
AI Technical Summary
Traditional soil permeability measurement methods have problems with priority flow and low measurement accuracy when measuring arsenic sandstone, and cannot intuitively display the changes in the particle pore structure of arsenic sandstone.
An experimental device including a sample tank, a moisture temperature sensor, a water supply system and a water collection bucket was designed. By installing a spiral distributed moisture temperature sensor on the outer wall of the sample tank and installing permeable stone, fine sand, gravel and gauze in the sample tank, visual measurement of the permeability characteristics of arsenic sandstone is achieved.
The device can more accurately measure the changes in moisture data of arsenic sandstone, improve the accuracy and visualization of the experiment, and ensure the accuracy and repeatability of the experimental results.
Smart Images

Figure CN119618951A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of soil permeability experiments, and in particular to an experimental device for testing the permeability characteristics of original arsenic sandstone. Background Art
[0002] Traditional field double-ring infiltration meters, knife-ring methods, etc., when measuring soil infiltration rate, are prone to preferential flow due to gaps between the infiltration meter ring wall and the soil. Since the degree of cementation between sand grains of arsenic sandstone is poor and the structural strength is low, such methods will affect the infiltration channels between soil particles of arsenic sandstone and the particle pore structure, which is not conducive to the implementation of repeated experiments, and the measurement accuracy is low. At the same time, it is impossible to intuitively see the changes in the particle pore structure of arsenic sandstone when it encounters water, and it is impossible to intuitively and clearly see the characteristics of the original arsenic sandstone.
[0003] Therefore, an experimental device for testing the permeability characteristics of original arsenic sandstone is needed, which can meet the experimental personnel's demands for visualization of the infiltration process, the accuracy requirements of the experiment, and the convenience of experimental operation by combining the soil characteristics of the original arsenic sandstone. Summary of the invention
[0004] The purpose of the present invention is to provide an experimental device for testing the permeability characteristics of original arsenic sandstone, aiming to solve the problems in the above-mentioned background technology.
[0005] To achieve the above-mentioned purpose, the present invention provides an experimental device for testing the permeability characteristics of original arsenic sandstone, comprising a sample tank, a moisture temperature sensor, a water supply system and a water collecting bucket, wherein the moisture temperature sensor is arranged on the outer wall of the sample tank, the water supply system is connected to the top of the sample tank, and the water collecting bucket is arranged below the sample tank;
[0006] A permeable plate is arranged at the bottom of the sample tank, a glass cover is arranged at the top of the sample tank, permeable stone and the arsenic sandstone sample to be tested are arranged inside the sample tank, the permeable stone is arranged above the arsenic sandstone sample to be tested, and fine sand, crushed stone and gauze are arranged in sequence below the arsenic sandstone to be tested.
[0007] Preferably, the sample jar is made of organic glass, and a layer of vaseline is applied on the inner wall of the sample jar.
[0008] Preferably, the sample tank comprises a first organic glass plate and a second organic glass plate, and the first organic glass plate and the second organic glass plate are connected by UV glue which is cured by ultraviolet light.
[0009] Preferably, four sensor mounting holes are arranged on the first organic glass plate, and the sensor mounting holes are spirally distributed along the height direction of the soil column, and the interval between each of the sensor mounting holes along the height direction of the soil column is set to 25 mm.
[0010] Preferably, there are four moisture temperature sensors, and the moisture temperature sensors are fixed on the first organic glass plate;
[0011] Each of the moisture and temperature sensors is connected to a data acquisition instrument. The moisture and temperature sensor comprises a probe and a probe head. The probe passes through the sensor installation hole and is inserted into the arsenic sandstone sample to be tested.
[0012] Preferably, a paraffin wax sealing layer is provided on the outer surface of the arsenic sandstone sample to be tested.
[0013] Preferably, the water supply system comprises a water supply tank and a flow meter, and two ends of the flow meter are respectively connected to the water supply tank and the sample tank.
[0014] Preferably, the thickness of the first organic glass plate and the second organic glass plate are both set to 10 mm, and the diameter is set to 61.8 mm.
[0015] Preferably, a method for using an experimental device for testing the permeability characteristics of undisturbed arsenic sandstone comprises the following steps:
[0016] S1. Use UV glue and irradiate with ultraviolet light to connect the first organic glass plate and the second organic glass plate, remove the excess UV glue at the joint, form a sample tank, and then apply a layer of vaseline on the inner wall of the sample tank;
[0017] S2. Use a soil cutter to trim the intact arsenic sandstone block into a cylindrical soil sample with a diameter of 61.8 mm and a height of 125 mm, so that the cylindrical soil sample matches the size of the sample jar. The cylindrical soil sample is the arsenic sandstone sample to be tested;
[0018] S3. Apply a layer of paraffin wax seal evenly around the arsenic sandstone sample to be tested;
[0019] S4, fix the sample tank on the permeable board, place a water collecting bucket with scale under the permeable board, put gauze, gravel and fine sand in the sample tank in sequence, then press the arsenic sandstone sample to be tested into the sample tank, place permeable stone on the top of the arsenic sandstone sample to be tested, and finally fix the glass cover on the top of the sample tank;
[0020] S5. Connect the water supply tank to the flow meter, and then use a water pipe to connect the flow meter to the sample tank;
[0021] S6. Install a moisture temperature sensor on the outer wall of the sample tank, insert the probe of the moisture temperature sensor completely into the sandstone sample to be tested, start the water supply tank, adjust the flow meter, and ensure that a continuous and stable water flow enters the sample tank. When the moisture temperature sensor at the top and the moisture temperature sensor at the bottom detect that the moisture content of the sandstone soil is consistent and the volume of water collected in the water collection bucket per unit time is the same, the moisture content of the sandstone sample to be tested reaches saturation, and then record the relevant data per unit time;
[0022] S7. The expression of the detection permeability coefficient is as follows:
[0023] K= Q×L
[0024] A×Δh
[0025] Where K is the permeability coefficient, A is the cross-sectional area of the arsenic sandstone sample to be tested, L is the height of the arsenic sandstone sample to be tested, Δh is the head difference, and Q is the stable seepage flow rate. Substitute the relevant recorded data per unit time to calculate the permeability coefficient of the arsenic sandstone to be tested.
[0026] Therefore, the present invention provides an experimental device for testing the permeability characteristics of original arsenic sandstone, which has the following beneficial effects: by using a transparent first organic glass plate and a second organic glass plate to form a sample tank, during the experiment, the changes in the particle pore structure of the arsenic sandstone when it meets water can be more intuitively seen, and the characteristics of the original arsenic sandstone can be intuitively and clearly seen, and the sample tank is detachable and can be reused. By installing a moisture temperature sensor on the outer wall of the sample tank, and the moisture temperature sensor is spirally distributed on the outer wall of the sample tank along the height direction of the soil column, the moisture data changes of the arsenic sandstone sample at different positions can be more accurately measured, so that the final experimental results are more accurate. According to the soil characteristics of arsenic sandstone, the degree of cementation between sand particles is poor and the structural strength is low. Fine sand, gravel and gauze are arranged under the arsenic sandstone sample to be tested to prevent the fine-grained soil of the arsenic sandstone from being washed away by water flow, protect the soil structure of the arsenic sandstone from being destroyed, and ensure the accuracy of the experimental results. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a schematic structural diagram of an experimental device for testing the permeability characteristics of original arsenic sandstone according to an embodiment of the present invention;
[0028] Figure 2 This is a schematic diagram of the structure of a sample tank according to an embodiment of the present invention;
[0029] Figure 3 This is a schematic structural diagram of a water-permeable plate according to an embodiment of the present invention;
[0030] Reference numerals
[0031] 1. Sample tank; 2. Moisture and temperature sensor; 3. Water supply system; 4. Water collecting bucket; 5. Permeable board; 6. Glass cover; 7. Permeable stone; 8. Arsenic sandstone sample to be tested; 9. Fine sand; 10. Gravel; 11. Gauze; 12. Vaseline; 13. First organic glass plate; 14. Second organic glass plate; 15. Sensor installation hole; 16. Paraffin sealing layer; 17. Water supply tank; 18. Flow meter. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0033] Unless otherwise defined, the technical terms or scientific terms used in the present invention should be understood by people with ordinary skills in the field to which the present invention belongs. The words "first", "second" and similar words used in the present invention do not indicate any order, quantity or importance, but are only used to distinguish different components. "Include" or "comprise" and similar words mean that the elements or objects appearing before the word include the elements or objects listed after the word and their equivalents, without excluding other elements or objects. "Connect" or "connected" and similar words are not limited to physical or mechanical connections, but may include electrical connections, whether direct or indirect. "Up", "down", "left", "right" and the like are only used to indicate relative positional relationships. When the absolute position of the described object changes, the relative positional relationship may also change accordingly.
[0034] Example
[0035] like Figure 1-3 As shown, the present invention is an experimental device for testing the permeability characteristics of original arsenic sandstone, comprising a sample tank 1, a moisture temperature sensor 2, a water supply system 3 and a water collecting bucket 4, wherein the moisture temperature sensor 2 is arranged on the outer wall of the sample tank 1, the water supply system 3 is connected to the top of the sample tank 1, the water collecting bucket 4 is arranged below the sample tank 1, a water permeable plate 5 is arranged at the bottom of the sample tank 1, and a glass cover 6 is arranged at the top of the sample tank 1 to prevent water evaporation from affecting the accuracy of the experimental results. 1 is provided with permeable stone 7 and arsenic sandstone sample 8 to be tested, the permeable stone 7 is arranged above the arsenic sandstone sample 8 to be tested, and fine sand 9, crushed stone 10 and gauze 11 are arranged in sequence below the arsenic sandstone sample 8 to be tested, the fine sand 9 and crushed stone 10 have good permeability, which help to accelerate the discharge of water, and the crushed stone 10 can also prevent the fine-grained soil of the arsenic sandstone from being washed away by the water flow, protecting the soil structure of the arsenic sandstone from being damaged, and the gauze 11 is used to collect the clay particles produced after the arsenic sandstone infiltration experiment.
[0036] The material of the sample tank 1 is set to be organic glass, and a layer of vaseline 12 is applied on the inner wall of the sample tank 1. Because the original soil of arsenic sandstone has obvious hard particles, it is necessary to apply vaseline 12 on the inner wall of the sample tank 1. Applying vaseline 12 on the inner wall can reduce the friction between the soil and the device, so that the soil can be more easily pressed into the sample tank 1, while keeping the original structure and composition of the arsenic sandstone sample 8 to be tested intact. The outer surface of the arsenic sandstone sample 8 to be tested is provided with a layer of paraffin sealing layer 16 to prevent moisture from flowing out from the surroundings of the arsenic sandstone sample 8 to be tested.
[0037] The sample tank 1 includes a first organic glass plate 13 and a second organic glass plate 14. The first organic glass plate 13 and the second organic glass plate 14 are connected by UV glue and cured by ultraviolet light. After curing, the first organic glass plate 13 and the second organic glass plate 14 can be separated after heating, and the UV glue at the original connection can be cleaned and reused.
[0038] Four sensor mounting holes 15 are arranged on the first organic glass plate 13. The sensor mounting holes 15 are spirally distributed along the height direction of the soil column. The interval between each sensor mounting hole 15 along the height direction of the soil column is set to 25 mm.
[0039] There are four moisture temperature sensors 2, which are fixed on the first organic glass plate 13. Each moisture temperature sensor 2 is connected to an external data acquisition instrument. The moisture temperature sensor 2 includes a probe and a probe. The probe passes through the sensor mounting hole 15 and is inserted into the arsenic sandstone sample 8 to be tested.
[0040] The water supply system 3 includes a water supply tank 17 and a flow meter 18 , and both ends of the flow meter 18 are connected to the water supply tank 17 and the sample tank 1 , respectively.
[0041] The thickness of the first organic glass plate 13 and the second organic glass plate 14 are both set to 10 mm, and the diameter is set to 61.8 mm.
[0042] A method for using an experimental device for testing the permeability characteristics of undisturbed arsenic sandstone comprises the following steps:
[0043] S1. Use UV glue and irradiate with ultraviolet light to connect the first organic glass plate and the second organic glass plate, remove the excess UV glue at the joint, form a sample tank, and then apply a layer of vaseline on the inner wall of the sample tank.
[0044] S2. Use a soil cutter to trim the intact arsenic sandstone block into a cylindrical soil sample with a diameter of 61.8 mm and a height of 125 mm, so that the cylindrical soil sample matches the size of the sample jar. The cylindrical soil sample is the arsenic sandstone sample to be tested.
[0045] S3. Apply a layer of paraffin wax seal evenly around the arsenic sandstone sample to be tested.
[0046] S4. Fix the sample tank on top of the permeable board, place a water collecting bucket with scale under the permeable board, put gauze, gravel and fine sand in the sample tank in turn, then press the arsenic sandstone sample to be tested into the sample tank, place permeable stone on top of the arsenic sandstone sample to be tested, and finally fix the glass cover on the top of the sample tank.
[0047] S5. Connect the water supply tank to the flow meter, and then use a water pipe to connect the flow meter to the sample tank.
[0048] S6. Install a moisture temperature sensor on the outer wall of the sample tank, insert the probe of the moisture temperature sensor completely into the sandstone sample to be tested, start the water supply tank, adjust the flow meter to ensure a continuous and stable flow of water into the sample tank, and when the moisture temperature sensor at the top and the moisture temperature sensor at the bottom of the sandstone sample to be tested detect that the moisture content of the sandstone soil is consistent and the volume of water collected in the water collecting bucket per unit time is the same, the moisture content of the sandstone sample to be tested reaches saturation, and then record the relevant data per unit time.
[0049] S7. The expression of the detection permeability coefficient is as follows:
[0050] K= Q×L
[0051] A×Δh
[0052] Where K is the permeability coefficient, A is the cross-sectional area of the arsenic sandstone sample to be tested, L is the height of the arsenic sandstone sample to be tested, Δh is the head difference, and Q is the stable seepage flow rate. Substitute the relevant recorded data per unit time to calculate the permeability coefficient of the arsenic sandstone to be tested.
[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. An experimental device for testing the permeability characteristics of undisturbed arsenic sandstone, characterized in that: It includes a sample tank, a moisture temperature sensor, a water supply system and a water collection bucket, wherein the moisture temperature sensor is arranged on the outer side wall of the sample tank, the water supply system is connected to the top of the sample tank, and the water collection bucket is arranged below the sample tank; A permeable plate is arranged at the bottom of the sample tank, a glass cover is arranged at the top of the sample tank, permeable stone and the arsenic sandstone sample to be tested are arranged inside the sample tank, the permeable stone is arranged above the arsenic sandstone sample to be tested, and fine sand, crushed stone and gauze are arranged in sequence below the arsenic sandstone to be tested.
2. The experimental device for testing the permeability characteristics of original arsenic sandstone according to claim 1, characterized in that: The material of the sample jar is set to be organic glass, and a layer of vaseline is coated on the inner wall of the sample jar.
3. The experimental device for testing the permeability characteristics of original arsenic sandstone according to claim 2, characterized in that: The sample tank comprises a first organic glass plate and a second organic glass plate, and the first organic glass plate and the second organic glass plate are connected by UV glue which is cured by ultraviolet light.
4. The experimental device for testing the permeability characteristics of original arsenic sandstone according to claim 3, characterized in that: The first organic glass plate is provided with four sensor installation holes, which are spirally distributed along the height direction of the soil column, and the interval between each of the sensor installation holes along the height direction of the soil column is set to 25 mm.
5. The experimental device for testing the permeability characteristics of original arsenic sandstone according to claim 4, characterized in that: There are four moisture temperature sensors, which are fixed on the first organic glass plate. Each moisture temperature sensor is connected to a data acquisition instrument. The moisture temperature sensor includes a probe and a probe. The probe passes through the sensor mounting hole and is inserted into the arsenic sandstone sample to be tested.
6. The experimental device for testing the permeability characteristics of original arsenic sandstone according to claim 5, characterized in that: The outer surface of the arsenic sandstone sample to be tested is provided with a paraffin sealing layer.
7. The experimental device for testing the permeability characteristics of original arsenic sandstone according to claim 1, characterized in that: The water supply system comprises a water supply box and a flow meter, and two ends of the flow meter are respectively connected to the water supply box and the sample tank.
8. The experimental device for testing the permeability characteristics of original arsenic sandstone according to claim 5, characterized in that: The thickness of the first organic glass plate and the second organic glass plate are both set to 10 mm, and the diameter is set to 61.8 mm.
9. A method for using the experimental device for testing the permeability characteristics of original arsenic sandstone according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Use UV glue and irradiate with ultraviolet light to connect the first organic glass plate and the second organic glass plate, remove the excess UV glue at the joint, form a sample tank, and then apply a layer of vaseline on the inner wall of the sample tank; S2. Use a soil cutter to trim the intact arsenic sandstone block into a cylindrical soil sample with a diameter of 61.8 mm and a height of 125 mm, so that the cylindrical soil sample matches the size of the sample jar. The cylindrical soil sample is the arsenic sandstone sample to be tested; S3. Apply a layer of paraffin wax seal evenly around the arsenic sandstone sample to be tested; S4, fix the sample tank on the permeable board, place a water collecting bucket with scale under the permeable board, put gauze, gravel and fine sand in the sample tank in sequence, then press the arsenic sandstone sample to be tested into the sample tank, place permeable stone on the top of the arsenic sandstone sample to be tested, and finally fix the glass cover on the top of the sample tank; S5. Connect the water supply tank to the flow meter, and then use a water pipe to connect the flow meter to the sample tank; S6. Install a moisture temperature sensor on the outer wall of the sample tank, insert the probe of the moisture temperature sensor completely into the sandstone sample to be tested, start the water supply tank, adjust the flow meter, and ensure that a continuous and stable water flow enters the sample tank. When the moisture temperature sensor at the top and the moisture temperature sensor at the bottom detect that the moisture content of the sandstone soil is consistent and the volume of water collected in the water collection bucket per unit time is the same, the moisture content of the sandstone sample to be tested reaches saturation, and then record the relevant data per unit time; S7. The expression of the detection permeability coefficient is as follows: Where K is the permeability coefficient, A is the cross-sectional area of the arsenic sandstone sample to be tested, L is the height of the arsenic sandstone sample to be tested, Δh is the head difference, and Q is the stable seepage flow rate. Substitute the relevant recorded data per unit time to calculate the permeability coefficient of the arsenic sandstone to be tested.